Natural compounds as antiatherogenic agents - Saqib, Uzma; Khan, Masood A.; Alagumuthu, Manikandan; Parihar, Suraj P.; Baig, Mirza S. (Cellular and Molecular Biology, 2021)
Atherosclerosis (AS) is a widespread pathological coronary heart disease (CHD), which, along with other cardiovascular diseases (CVDs), is the primary cause of global mortality. It is initiated by the accumulation of cholesterol-laden macrophages in the artery wall, thereby forming the foam-cells, the hallmark of AS. Increased influx of oxidized LDL and decreased efflux of free cholesterol from macrophages constitute major factors that mediate the progression of AS. Natural compounds treatment and prevention of AS being an effective approach for a long time. Currently, as interests in medicinally important natural products increased that including medicinal herbs, numerous studies on natural compounds effective forAS have been reported. In the current review, we shed light on the available plant-based natural compounds as AS modulators with underlying mechanisms that may lead to potential therapeutic implications.